L’auteur de la porte d’Amon à Karnak - Preys, René (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
The texts and images of the façade of the Ptolemaic gate of the second pylon of Karnak show similarities with the texts of the façade of the Ptolemaic temple of Esna. Numerous divine epithets are unique to those two compositions which also use similar grammatical expressions. The gate of Karnak was engraved during the first phase of the reign of Ptolemy VI Philometor. Work on the façade of Esna started five years later during the third phase of the reign. Comparisons between the two temple decorations suggest that both were composed by the same author.